Clinical usefulness of per-rectal portal scintigraphy by Tc-99m pertechnetate in evaluation of the severity of portal hypertension in cirrhotic patients - Sirianong Namwongprom (2018)
Introduction: Variceal haemorrhage is a potentially life-threatening complication in cirrhotic patients. Identification of patients at high risk for bleeding is particularly important. The aim of this study was to determine the clinical usefulness of per-rectal portal scintigraphy (PPS) in the evaluation of the severity of portal hypertension in cirrhotic patients, in terms of correlation between cirrhosis and the parameters of hepatic functional reserve, and identifying the difference of the portal shunt index (PSI) of the bleeding oesophageal variceal (BEV) patients and non-BEV patients. Methods: Portal circulations in 67 patients with cirrhosis and oesophageal varices were evaluated by Tc-99m pertechnetate PPS. Tc-99m pertechnetate (550 MBq) was instilled into the upper rectum, and dynamic images of upper abdomen were taken. Radioactivity curves for the liver and the heart were generated sequentially. Through the analysis of these curves, the PSI was determined. Results: The results, expressed as PSI, were: 11.4 +/- 98.4 percent (mean 66.8) in all 67 cirrhotic patients, 56.4 +/- 27.1 percent in cirrhotic patients without history of BEV, and 74.9 +/- 13.6 percent in cirrhotic patients with history of BEV. The PSI was significantly lower in cirrhotic patients without BEV than those with BEV (p-value equals 0.001). The PSI calculated with this method was correlated with the serum albumin, the serum bilirubin, the prothrombin time, and the Child-Turcotte-Pugh score. Conclusion: Tc-99m pertechnetate PPS has clinical usefulness as a noninvasive method of choice for quantitatively evaluating the severity of portal hypertension in cirrhotic patients.